Migration flows from south-east Europe in the last decade of the 20th century (with a special reflection on Bosnia and Herzegovina) - Salih Kulenovic; Izet Ibreljic (European Regional Science Association (ERSA), 2002)
Migration phenomenon from the region of South-East Europe has a character of long lasting process which intensity is changing depending on different circumstances. That process is a result of differences in development between the EU countries and countries in transition. In the last decade of the 20th century this process was specialy intensived and became a subject of great importance for scientific and political research. The goal of this paper is that on the base of available data view the consequences of previous migration flows from South-East Europe and analyze major couses of this process in the dimension of time and space. Beside that, this research needs in accordance with estimation of expected migration flows to indicate the possibilities of their slowing down so that some exact activities from the government of the european South-East countries could be taken. Of course, in the focus of this research is Bosnia and Herzegovina in which the migration process has been most intense.
Keywords: 330